Revalidation and redescription of Elachistocleis cesarii (Miranda-Ribeiro, 1920) (anura: microhylidae) - Toledo, Luís Felipe; Loebmann, Daniel [UNESP]; Haddad, Célio F.B. [UNESP] (Magnolia Press, 2010)
Elachistocleis cesarii (Miranda-Ribeiro, 1920), new combination, is revalidated and redescribed based on preserved specimens (syntype series) collected in the state of São Paulo. Furthermore, based on recently collected specimens, we increase the distribution of the species to the states of Minas Gerais and Goiás, Brazil. This species is found in open areas calling during the rainy season (from September to February for populations of the state of São Paulo). The advertisement call is described and some basic natural history data are provided. It distinguishes from all other species of the genus by the combination of the following characters: spotted belly, dominant frequency of the advertisement calls about 3.5 kHz, tympanum concealed, and presence of postcommisural glands. The advertisement call of Elachistocleis piauiensis, a similar species with spotted belly from the Caatinga Biome, was also described to compare it with the advertisement call of E. cesarii. Copyright © 2010 Magnolia Press.
Keywords: Amphibia; Anura; Elachistocleis cesarii; Gastrophryninae; Microhylidae